2018
DOI: 10.1017/pao.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture and analysis methods for enhancing long-term Brugia malayi survival, molting and motility in vitro

Abstract: Lymphatic filariasis is a neglected tropical disease caused by roundworm parasites such as Brugia malayi that spread via a mosquito vector. In vitro culture of these parasites provides controlled conditions to understand parasite biology and provides a cheaper way to screen potential micro-and macrofilaricides. Published studies have used a wide array of approaches and metrics regarding in vitro cultures of B. malayi; as a result, drawing comparisons and identifying the reasons why inability to reproduce outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Excised B. malayi derived from experimentally infected Meriones unguiculatus (Mongolian gerbils) exhibit rapid loss of viability in serum-supplemented media which is reflected by upregulation of a number of stress-response genes over the first five days in culture [42]. A recent study utilising image-based motion analysis demonstrated decline in female B. malayi PLOS NEGLECTED TROPICAL DISEASES motility (a late-stage indicator of in vitro fitness) begins at 5-7 days in optimised serum supplemented medium culture [43]. Due to this rapid demise in vitro, moderate automated throughput screening utilising motility phenotype as a readout of Brugia female macrofilaricidal activity has been limited to a three-day exposure window [44].…”
Section: Discussionmentioning
confidence: 99%
“…Excised B. malayi derived from experimentally infected Meriones unguiculatus (Mongolian gerbils) exhibit rapid loss of viability in serum-supplemented media which is reflected by upregulation of a number of stress-response genes over the first five days in culture [42]. A recent study utilising image-based motion analysis demonstrated decline in female B. malayi PLOS NEGLECTED TROPICAL DISEASES motility (a late-stage indicator of in vitro fitness) begins at 5-7 days in optimised serum supplemented medium culture [43]. Due to this rapid demise in vitro, moderate automated throughput screening utilising motility phenotype as a readout of Brugia female macrofilaricidal activity has been limited to a three-day exposure window [44].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of the eluate samples were conducted under a laminar flow cabinet to avoid contamination with particles and filaments in the air and a specific protocol was used to perform the FE-SEM/EDX analysis in order to avoid any contamination of the sample and instrument. The thread-like object in Figure 4d, however, has a similar morphology and size as a threadlike parasitic nematode (roundworm) of the superfamiliy Filarioridea [56,57]. Different Filarioridea nematodes exist and can infect humans, including Wuchereria bancrofti, Brugia malayi, Brugia timori, Onchocerca volvulus, Loa loa, Mansonella ozzardi, Mansonella perstans, Mansonella streptocerca and Brugia pahangi [58].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional 2-dimensional (2-D) culture systems were shown to support the early stages of development for few filarial nematodes in vitro , with some of these parasitic worms the cultures could be maintained long-term. The reported in vitro survival rates ranged from 33% after 77 days for Mansonella perstans L3 [ 17 ], 69% after 30 days for Brugia malayi L3 [ 18 ], and 60–90% for Loa loa L3 over 15 to 17.8 days in culture [ 19 , 20 ]. Recently, we described a novel 2-D in vitro culturing system based on a feeder layer of human umbilical vein endothelial cells (HUVEC) that has successfully supported the development of O .…”
Section: Introductionmentioning
confidence: 99%